Madagascar Economic Update : 2009 and Beyond - World Bank (Washington, DC, 2017)
At the end of 2008, prospects for Madagascar were high with a projected economic growth rate above 7 percent. About twelve months later, unfortunately, the situation looks very different with the impact of the global financial turmoil and the persistence of the political crisis. The local economy has been certainly in recession since the second quarter of 2009 and perspectives are even somber for 2010.